Rocky Mountain spotted fever in Mexico: past, present, and future. Issue 6 (June 2017) - Álvarez-Hernández, Gerardo; Roldán, Jesús Felipe González; Milan, Néstor Saúl Hernández; Lash, R Ryan; Behravesh, Casey Barton; Paddock, Christopher D
Summary: Rocky Mountain spotted fever, a tick-borne zoonosis caused by Rickettsia rickettsii, is among the most lethal of all infectious diseases in the Americas. In Mexico, the disease was first described during the early 1940s by scientists who carefully documented specific environmental determinants responsible for devastating outbreaks in several communities in the states of Sinaloa, Sonora, Durango, and Coahuila. These investigators also described the pivotal roles of domesticated dogs and Rhipicephalus sanguineus sensu lato (brown dog ticks) as drivers of epidemic levels of Rocky Mountain spotted fever. After several decades of quiescence, the disease re-emerged in Sonora and Baja California during the early 21st century, driven by the same environmental circumstances that perpetuated outbreaks in Mexico during the 1940s. This Review explores the history of Rocky Mountain spotted fever in Mexico, current epidemiology, and the multiple clinical, economic, and social challenges that must be considered in the control and prevention of this life-threatening illness.